Analisis Pengaruh Citra Merek, Ekuitas Merek, Promosi Dan Harga Terhadap Pengambilan Keputusan Pembelian Sepeda Motor Honda Vario (Studi Pengguna Honda Vario) (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis research aims to analyze the impact brand image, brand equity, promotion and price on purchasing decisions on honda vario . motorcycles. The samples used in this study refer to Ferdinand's Snowball sampling technique  that is, the researcher chose the Snowball sample to ensure that the respondents' criteria were in accordance with the specified and the sample consisted of 100 respondents. The results of this study simultaneously show that there is a significant influence between the variables of Brand Image, Brand Equity, Promotion and Price on Decision Making on the purchase of Honda Vario motorcycles. While the partial test results have a positive and significant effect between the Brand Image variables on purchasing decisions for Honda Vario motorcycles and Price on the decision to purchase a Honda Vario motorcycle while for the Brand Equity and promotion variable it partially has a positive and insignificant effect on purchasing decisions for Honda Vario motorcycles.Keywords: Brand image, Brand equity, Promotion, Price, Purchasing decisions